PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI SUKACA TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK TUNAGRAHITA KELAS VI DI SKH NEGERI 2 KOTA SERANG - Nurfadhilah, Askia; Asmiati, Neti; Maslahah, Sayidatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of using Sukaca animated video media on the early reading ability of students with intellectual disabilities (tunagrahita) in Grade VI at SKh Negeri 2 Kota Serang. The study employed a quantitative approach with a Single Subject Research (SSR) method using an A-B-A design. The subject was one male student with intellectual disabilities in Grade VI. Data were collected through an early reading ability test covering 18 sub-indicators of syllable and word reading. The results showed that in baseline-1 (A1), the mean percentage was 17% (stable across 4 sessions). During the intervention phase (B), scores increased progressively from 69% to 85%, with a mean level of 78.37% across 8 sessions. In baseline-2 (A2), the mean stabilized at 72% across 4 sessions, which was higher than baseline-1. The overlap percentage from A1 to B was 0%, and from B to A2 was 25%. These findings confirm that the use of Sukaca animated video media has a significant positive effect on the early reading ability of students with intellectual disabilities.Keywords: children with intellectual disabilities, early reading, Sukaca animated video, single subject research